PREVALENCE AND INTENSITY OF ECTOPARASITES IN GOLDFISH (Carassius auratus) AT MAJU MAPAN FARM, MAGELANG REGENCY - Qomariyah, Destya Nurul; Sari, Annisa Novita; Mujtahidah, Tholibah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Goldfish (Carassius auratus) at Maju Mapan Farm is one of the leading ornamental fish commodities with a high mortality rate due to disease. For this reason, this research aims to know about the type, prevalence, and intensity of ectoparasites at Maju Mapan Farm. The method in this research was random sampling for fish sampling 30 fish/pond. The type of parasites, prevalence, and intensity were analyzed descriptively and described in figures, tables, or graphs. This observation and identification showed that ectoparasites infected by goldfish at Maju Mapan Farm consisted of 3 types: Trichodina sp, Dactylogyrus sp, and Gyrodactylus sp. The types of ectoparasites that dominated both were Trichodina sp (96.11%), Dactylogyrus sp (3.61%), and Gyrodactylus sp (0.28%). Prevalence of ectoparasites was Trichodina sp (83.33%), Dactylogyrus sp (43.33%), and Gyrodactylus sp (6.67%). The intensity of ectoparasites were Trichodina sp (129 ind/fish), Dactylogyrus sp. (9 ind/fish), and Gyrodactylus sp (4 ind/fish). Trichodina sp. and Gyrodactylus sp. were commonly found in mucus, while Dactylogyrus sp. only infected goldfish in the gill organ. Prevalence and intensity of ectoparasites were found in goldfish with medium-stage infection at Maju Mapan Farm. The result of measuring water quality parameters was not optimal, causing ectoparasites to infect and multiply rapidly in goldfish at Maju Mapan Farm.